Analisis Dampak Lalu Lintas (Andalalin) di Kawasan Gedung Kampus Universitas Prima Indonesia - Ulfa Dwiyanti Pane; Nurmaidah Nurmaidah (Universitas Medan Area, 2020)
Traffic Impact Analysis is a study of traffic impacts that occur due to changes in traffic arrangements due to a development or development in a particular region. To anticipate the influence of a large enough traffic, it is necessary to conduct a Traffic Impact Analysis. This research was conducted to determine the characteristics of the road network and move students to the UNPRI campus. Analyze how much new trip generation requires traffic engineering and traffic management. This research was conducted by quantitative descriptive method. The discussion is carried out by describing the problems that exist in sequence and then analyzed to get solutions to problems. Trip generation and attraction resulting from UNPRI Medan Faculty of Medicine campus building activities are predicted to generate trips of 183 smp /hour, and attract trips of 183 smp/hour. The road segment directly affected by the activities of the Medan Medical Faculty UNPRI is Jalan Gelas. Based on the results of the analysis conducted in the prediction of Jalan Gelas will experience changes in traffic performance. The worst performance of the 2019 basic road segment occurred in the segment 2 Ayahanda road with a Degree of Saturation of 0.73 or Level of Service D. While the performance of the road segment on a Gelas Road with a DS of 0.43 or Level of Service B.